Inhibitory Effect of Cranberry Fruit Extracts on Adhesion of Urinary Tract Infection Bacteria - Rammo, Rita N N (Al-Nahrain Journal of Science, 2013)
In vitro adhesion of bacteria to uroepithelial cells in the presence of cranberry methanol and water base extracts has been studied. Microorganisms taken from patients with urinary infections were (48%) Escherichia coli, (26%) Klebsiella pneumoniae, (16%) Proteus mirabilis, and (10%) Staphylococcus aureus. The adhesion of bacteria to uroepithelial cells in the presence of cranberry methanol base extract with varying concentrations showed high inhibition at concentrated extract (25 mg/ml) with S. aureus and E. coli being mostly affected and to a lesser extent with P. mirabilis and K. pneumoniae. Inclusion of water in the extraction of cranberry, showed an inhibition effect of the concentrated extract (25 mg/ml) as being ca. 22% less effective than the methanol base extract. Results are discussed in terms of bacterial structure and the disruption of binding between the receptors of uroepitheilal cells.